Kinerja Pegawai Kecamatan Merigi Sakti Kabupaten Bengkulu Tengah Dalam Pembuatan Surat Keterangan Tanah - Martin, Roy; Imanda, Antonio; Sariningsih, Marida; Rikardo, Yanuar (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research purpose is to find out the performance of employees in creating land certificate at Merigi Sakti District of Seluma regency. This research is descriptive qualitative research. Data are collected by using interview, observation and documentation. In this researchthere are 4 informants, 2 people as key informants and the other 2 as main informant. This research use performance theory (Mahsum, 2006: 7) with results as below: 1. The input: in making land certificate, there was no any free people have to pay, everything is free because there was an instruction from regency government, 2. Process: in making land certificate, the process was not completed on time because the certificate finished more than one month and because of that society started not to believe with this officers, 3. The output, the officer doesn’t have target to indicate how many certificates must be finished because it depends an the number of requested people. 4. Outcome the quality of the certificate is better than before and the officers are skilled based on their skill background, 5. Benefit, the awareness level of society about the benefit from certificate are quite high almost all land have certificate personally, 6. Impact, the positive inpcat from having land certificate is about the legal low of private land ownership which regulated by laws of land by nation, the price of landis high and can be used as a collateral to finance department to simplity the loan.